The Effect of Tax Modernization, Tax Rates, and Tax Sanctions on MSME Taxpayer Compliance in the Medan Area District - Evelyn Kosumo; Juliandi Sahputra; Hermawan Sutanto (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
Determining the effect of tax modernization, tax rate, and tax sanction on taxpayer’s compliance became the aim of this study by utilizing quantitative approach as its research method. This study utilize primary data that had been gathered through the distribution of questionnaires to taxpayers who were Micro, Small, and Medium Enterprise (MSME) owners in the Medan Area sub-district. Non-Probability Sampling with an Accidental Sampling approach was used as the sampling technique in this study, with a sample size of 100  from the population of 7.263 MSME owners. Multiple Linear Regression Analysis is used as its analysis technique, executed in the SPSS 26 software. The analysis results found the tax modernization, tax rate, and tax sanctions to have had a positive and significant effect, both simultaneouslyand partially, on the MSME taxpayer’s compliance in the Medan Area sub-district.